IoT sensors integrated with the distributed protocol IOTA/Tangle: Bosch XDK110 use case - Silvano, Wellington; De Michele, Daniel; Trauth, Daniel; Marcelino, Roderval (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2020: Anais do X Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2020)
Decentralized systems can provide privacy, security, and immutability without relying on a central authority. In the context of the Internet of Things, Distributed Ledger Technologies (DLT) can be important facilitators for implementing IoT economies. IOTA is a public DLT, which was created to provide support for the Internet of Things. The IOTA protocol enables high transaction throughput at zero cost, while also being highly scalable. These characteristics make it possible to collect sensor data with transparency and security, using a distributed public network. Despite the great potential of IOTA as a distributed protocol for sensor data, there are still no studies that demonstrate how the connection between sensors and IOTA can occur, and what the characteristics and limitations of the system are. We began exploratory technological research which includes the modeling of a system that allows the integration of IOTA with sensors, using IOTA as the data layer. An implementation of the model has been developed, based on data collection from the Bosch XDK110 multisensor and a storage/visualization application. Because the IOTA protocol requires Proof of Work to send and broadcast data over the network, which takes a few seconds, it is not possible to have granular live data from sensors directly interacting with the DLT. However, we will study the case of an application that allows for this by buffering data and inserting it to the IOTA network at a rate that nodes can handle.